2005
DOI: 10.1089/hum.2005.16.1484
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Direct Administration of AAV2CUhCLN2, a Candidate Treatment for the Central Nervous System Manifestations of Late Infantile Neuronal Ceroid Lipofuscinosis, to the Brain of Rats and Nonhuman Primates

Abstract: Late infantile neuronal ceroid lipofuscinosis (LINCL), a pediatric autosomal recessive neurodegenerative lysosomal storage disorder, results from mutations in the CLN2 gene and consequent deficiency in tripeptidyl-peptidase I (TPP-I) and progressive destruction of neurons. We have previously demonstrated that CNS gene transfer of AAV2(CU)hCLN2 (an AAV2-based vector expressing the human CLN2 cDNA) in rats and nonhuman primates mediates long-term TPP-I expression in the CNS neurons [Sondhi, D., Peterson, D.A., G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 67 publications
3
28
0
Order By: Relevance
“…Studies of experimental animal models and humans have shown that a significant challenge to providing effective gene therapy for the CNS manifestations of the lysosomal storage disorders is that most of these disorders diffusely affect the CNS, and thus effective therapy requires delivery of the product of the therapeutic vector throughout the brain (Beck, 2007;Sondhi et al, 2001). This challenge is further compounded by the physical limitations of administration of gene therapy vectors to the human CNS, including the number of burr holes that can be placed in the skull, the volume that can be administered per min, and the total time of anesthesia that can be used safely (Crystal et al, 2004;Hackett et al, 2005). Finally, corrective gene therapies for neurodegenerative diseases are not restorative but rather halt disease progression, making delivery prior to disease onset an important objective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of experimental animal models and humans have shown that a significant challenge to providing effective gene therapy for the CNS manifestations of the lysosomal storage disorders is that most of these disorders diffusely affect the CNS, and thus effective therapy requires delivery of the product of the therapeutic vector throughout the brain (Beck, 2007;Sondhi et al, 2001). This challenge is further compounded by the physical limitations of administration of gene therapy vectors to the human CNS, including the number of burr holes that can be placed in the skull, the volume that can be administered per min, and the total time of anesthesia that can be used safely (Crystal et al, 2004;Hackett et al, 2005). Finally, corrective gene therapies for neurodegenerative diseases are not restorative but rather halt disease progression, making delivery prior to disease onset an important objective.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, corrective gene therapies for neurodegenerative diseases are not restorative but rather halt disease progression, making delivery prior to disease onset an important objective. With these limitations in mind, three basic strategies have been employed to achieve therapeutic levels of gene expression throughout the brain: identifying gene transfer vectors that will diffuse through the CNS more effectively (Cearley and Wolfe2006;Deglon and Hantraye2005;Shevtsova et al, 2005;Sondhi et al, 2007), optimizing the method of delivery and volume and rate of infusion (Chen et al, 1999;Hackett et al, 2005;Hsich et al, 2002), and administration at an earlier time point, when the brain is smaller and immature (Bostick et al, 2007;Broekman et al, 2007;Daly et al, 1999;Griffey et al, 2006;Li and Daly2002;Passini et al, 2003;Passini and Wolfe2001;Rafi et al, 2005;Shen et al, 2001;Waddington et al, 2004). Studies from our laboratory and others have identified several serotypes of adeno-associated virus (AAV) vectors that are more effective than the first generation vectors used for CNS gene transfer (Broekman et al, 2006;Burger et al, 2005;Cearley and Wolfe2006;Harding et al, 2006;Sondhi et al, 2007;Taymans et al, 2007), the parameters for optimal administration of vectors to the CNS have been established (Chen et al, 1999;Hackett et al, 2005;Hsich et al, 2002) and several studies have shown that administration earlier in life results in an advantage over therapy in older animals (Bostick et al, 2007;Broekman et al, 2007;Daly et al, 1999;Griffey et al, 2006;Li and Daly2002;Passini et al, 2003;Passini and Wolfe2001...…”
Section: Introductionmentioning
confidence: 99%
“…Initial studies examining the expression of TPPI by recombinant AAV and other viral vectors demonstrated high levels and widespread expression of the protein throughout the central nervous system (CNS) of healthy rodents [7,8]. More recently, AAVmediated gene therapy has been evaluated in a mouse model for LINCL.…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and clinical studies have shown the feasibility and initial promise of using an adeno-associated virus (AAV) to transfer the human CLN2 cDNA to the brains of children with LINCL (Crystal et al, 2004;Hackett et al, 2005;Sondhi et al, 2005Sondhi et al, , 2007Passini et al, 2006;Worgall et al, 2008;Souwedaine et al, 2010). Preclinical studies with rodents showed that administration of the human CLN2 cDNA by means of an AAV2-based vector (AAV2 hCLN2) was associated with a decrease in the abnormal accumulation of storage material in CNS neurons (Hackett et al, 2005;Sondhi et al, 2005;Passini et al, 2006).…”
Section: Cns Gene Transfer For Linclmentioning
confidence: 99%
“…Preclinical studies with rodents showed that administration of the human CLN2 cDNA by means of an AAV2-based vector (AAV2 hCLN2) was associated with a decrease in the abnormal accumulation of storage material in CNS neurons (Hackett et al, 2005;Sondhi et al, 2005;Passini et al, 2006). This was followed by a clinical study in which the AAV2hCLN2 vector was administered directly to the CNS of 10 children with LINCL of severe or moderate severity in a neurosurgical procedure involving six burr holes, catheter insertion, and infusion of the vector in a total of 12 sites over several hours (Worgall et al, 2008;Souweidane et al, 2010).…”
Section: Cns Gene Transfer For Linclmentioning
confidence: 99%